Proses Pengadaan Barang Event "Floriculture Indonesia International Expo" Divisi Procurement PT Fasen Creative Quality - Revica Chika Wahyudi; Firman Syah (Bisnis Event, 2026)
The rapid development of the event industry in Indonesia, especially in the exhibition sector, has become an importantplatform for companies to introduce products, establish business networks, and attract investors and tourists. Largescale exhibitions have a positive impact on the local economy, including the transportation, accommodation, andhospitality sectors. This study aims to analyze the process of demand to procurement of goods at events carried out bythe procurement division and identify the main obstacles faced by the procurement division in the procurement processfor exhibition events, especially in terms of time, cost and quality of goods. The data analysis method used by the authoris a descriptive qualitative method. The procurement process in the procurement division includes several stagesincluding the vendor search and selection process, the vendor payment process and the goods receipt process duringloading. Each process has its own procedure. In carrying out its duties, the procurement division faces several obstaclesthat often occur, namely the difficulty in finding vendors that meet needs, long communication with vendors, differencesin expectations between vendors and event organizers, price negotiations and internal decision-making that take a longtime, goods sent do not match specifications, quantity, or are damaged, and technical obstacles, but all these obstaclescan be overcome by implementing effective solutions and taking anticipatory steps.